Chlorophyll fluorescence imaging can reflect development of vascular connection in grafting union in some Solanaceae species - Penella, Consuelo; Pina, Ana; San Bautista, Alberto; López-Galarza, Salvador; Calatayud, Ángeles (2018)
Graft union development in plants has been studied mainly by destructive methods such as histological studies. The aim of this work was to evaluate whether the chlorophyll fluorescence imaging (CFI) technique is sensitive enough to reflect changes at the cellular level in different Solanaceae grafted plants 30 d after grafting, when both grafted partners were well fused and strong enough in all plant combinations. The pepper cultivar 'Adige' was grafted onto different Capsicum spp. accessions typified with different compatibility degrees; eggplant was grafted on Solanum torvum and pepper homografts as compatible unions; pepper was grafted on S. torvum and on tomato as incompatible unions. 'Adige'/'Adige' and 'Adige'/pepper A25 showed a higher maximum quantum efficiency of PSII associated with higher values of actual quantum efficiency of PSII and photochemical quenching as well as with vascular regeneration across the graft interface. Our results highlighted that CFI changes reflected histological observations in grafted Solanaceae plants.